The clinician’s imperative: Integrating AI for the future of care - N Shah, Jay (Journal of Chitwan Medical College, 2026)
Artificial Intelligence (AI) has moved beyond a technological innovation to become a fundamental pillar of healthcare research and delivery. It offers significant opportunities for daily clinical practice and medical education. The transition requires a re-look of how we train the next generation of physicians to develop competency in the integration of AI for health education, research, and health care delivery.